Analisis Kesalahan Siswa dalam Menyelesaikan Soal Aritmatika Sosial - Apri Kurniawan; Nelly Fitriani (Departement of Mathematics Education, 2020)
This research is motivated by the importance of social arithmetic material in mathematics especially for students as educational subjects in daily life, while the aim is to analyze students’difficulties in solving social arithmetic questions in the form of contextual questions. This study is classified as a qualitative descriptive study that illustrates the ability of students to solve social arithmetic problems in which the question is based cognitive bloom. The population in this study were all eighth grade junior high school students in West Bandung regency whose samples were selected randomly in Mahardika Middle School as many as 31 people. The data was obtained by testing 8 test question containing the cognitive bloom domain with 3 C3 details, 3 C4 questions and 2 C5 questions. The results showed that there were 1 people with high ability, 2 people with moderate abilities, and 28 people with low abilities with various errors including misconceptions, principle errors, and data operation errors, while the average acquisition rate was 25,7%. It can be concluded that the ability of students to solve problems is still relatively low so that efforts are needed to improve abilities.